2005
DOI: 10.1002/eji.200425836
|View full text |Cite
|
Sign up to set email alerts
|

Rapid in vivo analysis of mutant forms of the LAT adaptor using Pax5‐Lat double‐deficient pro‐B cells

Abstract: Following injection into recombinase‐activating gene‐deficient (Rag1–/–) mice, pro‐B cells lacking the Pax5 transcription factor (Pax5–/–) develop into most major hematopoietic lineages, with the notable exception of B cells. We assessed whether Pax5–/– pro‐B cells that were also rendered deficient for the linker for activation of T cells (LAT), an adaptor essential for T cell receptor signaling, can be used for the rapid in vivo analysis of mutant forms of LAT. We showed that Pax5–/– Lat–/– pro‐B cell lines c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Previously, the Pax5‐deficient proB cell system has successfully been used to analyze mutant forms of the LAT adaptor in vivo 37. Herein, we have demonstrated that TCR‐β chains isolated from γδ T cells can very efficiently participate in αβ T‐cell development and can give rise to functional T cells.…”
Section: Discussionmentioning
confidence: 93%
“…Previously, the Pax5‐deficient proB cell system has successfully been used to analyze mutant forms of the LAT adaptor in vivo 37. Herein, we have demonstrated that TCR‐β chains isolated from γδ T cells can very efficiently participate in αβ T‐cell development and can give rise to functional T cells.…”
Section: Discussionmentioning
confidence: 93%
“…Samelson and coworkers [12] showed that mutation of this single tyrosine affects none of the intracellular signals triggered upon TCR engagement. Moreover, using a system in which Rag-deficient mice were reconstituted with T cell precursors expressing the LAT Y235F mutant (in which tyrosine 235, the equivalent to tyrosine 226 in mice, was substituted by phenylalanine), this mutant form of LAT was capable of reconstituting normal T cell development [43]. Therefore, it is likely that the specific signaling phenotype observed in JCaM2.5 cells expressing mutant LAT 5S/A cannot be fully recapitulated by the expression of LAT molecules expressing a mutation of tyrosine 226, suggesting that the conserved serine motifs may have a direct role in recruiting some effectors or adaptors.…”
Section: Discussionmentioning
confidence: 98%
“…B. Malissen (Marseille, France) discussed the activation pathway that is initiated by TCR ligation. When TCR encounters an antigen presented by an MHC protein, the tyrosine kinase Zap70 is activated, the linker for activation of T cells (LAT)—a raft‐anchored molecule—is phosphorylated, and a platform for further molecular recruitment is created (Ardouin et al , 2005). Malissen likens LAT to “a protein fishing line”; flexible and extended in the cytosol to allow a large capture radius.…”
Section: Introductionmentioning
confidence: 99%